2010
DOI: 10.1007/s11606-010-1375-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Verification Bias on the Sensitivity of Fecal Occult Blood Testing: a Meta-Analysis

Abstract: OBJECTIVES: There is controversy regarding the sensitivity of fecal occult blood tests (FOBT) for detecting colorectal cancer. Many of the published studies failed to correct for verification bias which may have increased the sensitivity. METHODS: A meta-analysis of published studies evaluating the sensitivity and specificity of chemical-based FOBT for colorectal cancer was performed. Studies were included if both cancer and control subjects underwent confirmatory testing. We also included studies that attempt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…Furthermore, it was reported that gFOBT had a low positive predictive value and over 80% of its positive results were false 42. A meta‐analysis that evaluated the effect of verification bias on the sensitivity and specificity of gFOBT showed the existence of verification bias, which could largely affect the estimates of gFOBT, the pooled sensitivity and specificity of the studies without verification bias turns out to be 0.36 (95% CI = 0.25–0.47) and 0.96 (95% CI = 0.94–0.97) 43. In our head‐to‐head comparison of fecal PKM2 and gFOBT for diagnosis of CRC, all the patients accepted the colonoscopy exam as the reference test; thus, the results could be thought of as nonverification bias.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that gFOBT had a low positive predictive value and over 80% of its positive results were false 42. A meta‐analysis that evaluated the effect of verification bias on the sensitivity and specificity of gFOBT showed the existence of verification bias, which could largely affect the estimates of gFOBT, the pooled sensitivity and specificity of the studies without verification bias turns out to be 0.36 (95% CI = 0.25–0.47) and 0.96 (95% CI = 0.94–0.97) 43. In our head‐to‐head comparison of fecal PKM2 and gFOBT for diagnosis of CRC, all the patients accepted the colonoscopy exam as the reference test; thus, the results could be thought of as nonverification bias.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis comparing the diagnostic accuracy of FOBT for colorectal cancer found that the pooled sensitivity of FOBT without verification bias was significantly lower than those studies with this bias (0.36 vs 0.70). The pooled specificity of the studies without verification bias was also higher (0.96 vs 0.88) 4. The authors concluded that ‘the sensitivity of guaiac-based FOBT for colorectal cancer has been overestimated as a result of verification bias.…”
Section: Impactmentioning
confidence: 97%
“…The guaiac-based FOBT (gFOBT) is the typical test of the early FOBT products. However, the later developed faecal immunochemical test (FIT) for haemoglobin has been shown to be better than the original gFOBT [1]. It has better sensitivity and specificity for predicting colorectal neoplasms in an asymptomatic population [2].…”
Section: Introductionmentioning
confidence: 99%